2008
DOI: 10.1063/1.2953521
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of carbon nitride deposition from CH4∕N2 glow discharge plasma beams using optical emission spectroscopy

Abstract: The properties of plasmas in a CH4∕N2 dc abnormal glow discharge with the percentage of methane from 1% to 20% have been studied in order to understand the effect of precursor incorporation into the carbon nitride (CNx) films. The appearance of CN radicals as well as C2, CH, and NH has been revealed by optical emission spectroscopy (OES). The evolution of CN, N2, N2+, and C2 emission lines from mixed CH4∕N2 and pure N2 plasma on changing mixture ratio and polarity of discharge-field has been studied. The possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…By comparing the five images (Figure 1 a,b,c,d,e), it could be found that the average height and bottom diameter of the as-grown CNNCs increase quickly, but their distribution density changes inapparently as the CH 4 feeding gas increases. The above phenomena could be explained by that the supersaturation conditions necessary for the nucleation of the CNNCs could be more easily satisfied for a very little CH 4 supply [ 17 ]. When the CH 4 supply increases, the CN radicals in the plasma also increase and the N 2 + or N + etching effects become weaker relatively, which will lead to the increment of the growth rate of the CNNCs and their more intact conical shape (Figure 1 d,e).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By comparing the five images (Figure 1 a,b,c,d,e), it could be found that the average height and bottom diameter of the as-grown CNNCs increase quickly, but their distribution density changes inapparently as the CH 4 feeding gas increases. The above phenomena could be explained by that the supersaturation conditions necessary for the nucleation of the CNNCs could be more easily satisfied for a very little CH 4 supply [ 17 ]. When the CH 4 supply increases, the CN radicals in the plasma also increase and the N 2 + or N + etching effects become weaker relatively, which will lead to the increment of the growth rate of the CNNCs and their more intact conical shape (Figure 1 d,e).…”
Section: Resultsmentioning
confidence: 99%
“…In this mode, the nickel catalyst layer first melts and fragments into separated hemisphere-like islands under heating of the abnormal glow discharge plasma over the substrate. Then, the incipient CNNCs are formed on the nickel islands due to the deposition of precursors such as CN species, nitrogen atoms, and C 2 species from the discharge plasma [ 17 ]. As the CN radicals and other reactive species continue to attach, the heights and lateral diameters of the CNNCs increase simultaneously.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This time can be viewed as the "relaxation" time for the gas concentration to reach new equilibrium state of newly set proportion of the gases in the chamber. The optical emission spectroscopy (OES, OceanOptics 4000 instrument) was used for the precise determination of such relaxation time by the dynamic of change of integrated intensity of CN band (violet band system, Δv = -1) near 421 nm [50,51]. This particular band was chosen due to absence of interfering peaks of standard H2-CH4 plasma (see Fig 2a).…”
Section: Methodsmentioning
confidence: 99%
“…This may be why the main bodies of the CN x nanocones grown previously are amorphous other than crystalline C 3 N 4 (only very little C 3 N 4 crystallites exist at the places adjacent to the Ni-catalyst) [32]. Because the precursors from relatively high levels of CH 4 and N 2 inlets (without H 2 ) are mainly composed of CN species, nitrogen atoms and very few C 2 species [36], the deposition of these precursors will lead amorphous CN x other than crystalline C 3 N 4 which need the reaction between atomic C and N without other species involved. Here, at a high CH 4 inlet, H + -sputtering of the graphite frame would be suppressed by the reactions between H + and CH n -(n<4), which led to the growth of silicon nanocone arrays for the silicon substrate is more easily etched by N + /N 2 + and H 2 + .…”
Section: The Growth Mechanisms Of Different Kinds Of Nanoconesmentioning
confidence: 98%